Nursery upweller type has minimal impact on subsequent grow-out of Eastern oysters (Crassostrea virginica) - Tarnecki, Andrea M.; Landry, Kevin; Rikard, Scott (Frontiers in Aquaculture, 2023)
Demand for oysters in the premium half-shell market drives the need for research to optimize and improve oyster aquaculture production methods. After setting, oysters are typically maintained in nursery upwellers that provide nutrients and oxygen while removing waste. They remain in the nursery until they are large enough to be deployed in aquaculture gear. Land-based upweller systems include silo and bottle upwellers, with bottles requiring less space and maintenance. However, it is unknown if upweller type influences oyster growth, shape, or survival after field deployment. This study reared Eastern oysters, Crassostrea virginica, to 2 mm in silo or bottle upwellers and deployed them to floating bags for a six-week grow-out period. Oysters were sampled initially, then size graded, counted, and redeployed every two weeks. Changes in growth parameters, quality ratios, survival, and hinge backbend deformity prevalence were determined after six weeks. Initially, silo-reared oysters were larger than those reared in bottles, likely due to the need for flow rate optimization and/or the tumbling action that breaks the fragile growing edge of the shell. Despite these initial differences, there were minimal size differences between upweller types after six weeks of growth in the field. There were no significant differences in survival, hinge backbend abnormality prevalence, or size class distribution between upweller types. These results indicate that upweller choice has minimal impact on the grow-out phase of oyster production and both systems are acceptable for Eastern oyster production in the northern Gulf of Mexico.